PELUANG INTENSIFIKASI AGROFORESTRI PEKARANGAN DENGAN INTRODUKSI WIJEN (Sesamun indicum L.) DI KAWASAN PERBUKITAN MENOREH KULON PROGO - , JUNAIDAH; , Dr. Priyono Suryanto, S.Hut, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The existence of homegarden has a strategic position in human life and currently is as an important part of trees outside of the forest. One of the efforts to sustain the homegarden is through intensification. The homegarden intensification can be conducted by introducing a new potential species, one of which is sesame (Sesamun indicum L.). This research is aimed at (1) identifying the influence of physical and chemical environmental condition of homegarden agroforestry on the growth, morphology, physiology, production, and quality of the sesame, (2) identifying the opportunity of introducing the sesame on 3 (three) growth levels of the homegarden agroforestry. The experimental design employed a nested plot sampling. The main plot consisted of 3 (three) development levels of homegarden agroforestry, namely early homegarden agroforestry (shading intensity = 0-30 %), intermediate homegarden agroforestry (shading intensity = 31-60 %) and advanced homegarden agroforestry (shading intensity > 60 %). The nested plot consisted of 3 (three) sesame varieties, namely Sbr 1, Sbr 2 and Sbr 4. Data of observation and measurement results were analyzed using multiple regression. The independent variables included shading intensity, soil pH, as well as N, P and K contents of the soil. The dependent variables included growth response, morphology, physiology, production and quality of the sesame. The research results indicate that in general heavier shading intensity reduced the rate of growth and physiological activities of the plant so that the production of the sesame decreased. Generally, the soil pH which tended to be neutral and N,P and K contents of the soil which got higher (until certain limit) increased the rate of growth and physiological activities of the plant so that the production of sesame increased. The biggest opportunity of the intensification was the early homegarden agroforestry by using sesame Sbr1 with the production potency of 519,98 kg/ha. The land could be intensified by giving organic materials, regulating species composition and planting distance, and intensive maintenance.